Professores da Educação de Jovens e Adultos construindo trajetórias de sucesso: um estudo a partir da psicogenética walloniana - Fernandes, Ademilson Aparecido Tenório (2011)
The present study discusses how the affectiveness is expressed on teaching performance, considering the contexture of Young and Adults Education, the teachers perception as well as their students perception. It goes beyond the descriptive characteristics; it also considers how the teaching performance can canalize the affectiveness in service of knowledge, when recognizing the integration cognitive-affective. The individuals of this research are: a Portuguese Teacher, a Science Teacher and their 36 students, who are registered at an EJA final stage classroom in a Public School of São Paulo. The information were produced by video-recording analysis sections and were inspired by autoscopy works. This methodology beyond contemplating the interaction between teachers and students in the classroom and the critical analysis of the students and teacher about the experienced situation, also allowed the individuals to express how they were affect by the concrete situations. The classes impressionistic observation strengthens the methodological necessity to clarify some phenomenon occurred in the classroom as well as some situations captured in the video-records. The information analysis was conducted in the light of psycho-genetic theory of Henri Wallon. The analysis revealed the teachers and the students perception about the teaching performance regarding the classes planning, the importance of knowing the student and respecting his acquaintance rhythm, the commitment and the availability of the teachers and the relationship of the teachers with the curricular discipline and the evaluation. It also revealed the reverberation of this performance in the process teaching- acquaintance